Optimizing the Selection of BTQ Learning Methods at UIN Syekh Wasil Kediri Through the Simple Additive Weighting Method - Mubarokah, Lailatul; Hamidah, Dwi Ananda; Vindiani, Poppy Nabila; Ilmiyah, Nur Fadilatul (Faculty of Tarbiyah, Institut Agama Islam Negeri (IAIN) Kediri, Indonesia, 2025)
The selection of an appropriate Quranic Recitation and Writing (BTQ) method has a direct and significant impact on students’ academic progress, as BTQ is a mandatory prerequisite for participating in the Community Service Program (KKN) at UIN Syekh Wasil Kediri. However, the current process for selecting a BTQ method has not been based on a structured and objective approach. Consequently, many students experience difficulties in passing the BTQ examination, which in turn delays their participation in KKN. This quantitative descriptive study aims to analyze the application of the Simple Additive Weighting (SAW) method in determining the most effective BTQ method for students at UIN Syekh Wasil Kediri. The SAW method was selected for its capability to produce accurate results through a systematic process of evaluating and ranking alternatives. The BTQ method selection process was evaluated based on eight criteria: ease of material delivery by the instructor, structured learning system, availability of supporting textbooks, tajweed instruction, introduction to makharij al-huruf, use of melody in recitation, instructor recruitment mechanism, and grading level advancement system. The SAW calculations were conducted by a decision maker who assigned weights to these criteria. Evaluation data were collected through questionnaires administered to twelve respondents to assess six alternative BTQ methods. Based on the SAW calculation results, the recommended ranking of BTQ methods is as follows: Qira’ati, Ummi, Yanbu’a, Tilawati, Iqra’, and Jami’ati. This research is expected to contribute significantly to the BTQ program at UIN Syekh Wasil Kediri by addressing challenges related to BTQ graduation rates and delays in KKN participation.